The efficient reinforcement of polyamide 1212 in nitrile rubber via the formation of fibrous structures - Zhou, Huajin; Jia, Zhenyu; Jiang, Ming; Bao, Haifeng; Huang, Leping; Cai, Ziqing (Materials research express, 2019)
Nitrile rubber (NBR) blends with excellent performance have always been a hot research topic in oil drilling process. Due to the excellent properties and compatibility of polyamide 1212 (PA1212), it provides an opportunity for preparation of high-performance NBR/PA1212 blends. In this paper, NBR/PA1212 blends were prepared by the three-step molding process. Based on experimental results, it was found that PA1212 has a prominent reinforcement effect in NBR matrix. The change of these mechanical properties was investigated from aspects of the crystal structure, crystallinities, and phase morphology. The formation of fibrous structure of PA1212 phase presents the best reinforcement effect in the polymer blends. Meanwhile, the formation mechanism of the special phase structure induced by the three-step process is deeply expounded.